Analysis of Acid Organic Compounds in Soil by Complexation Coupled with in situ Derivatization - Zhang, Li; Zhang, Chenling; Gui, Jianye; Zhang, Yongtao; Li, Xiaoya; Zhao, Guoxing; Tian, Laisheng (Asian Journal of Chemistry, 2015)
A method that in situ derivatization and extraction of acidic organic compounds in soil was developed with Na4-EDTA as complexing agent and 2,3,4,5,6-pentafluoro-benzyl bromide as derivatization agent. Derivatization products were sensitively determined by gas chromatography-negative chemical ionization mass spectrometry. Acidic organic compounds reacted with Na4-EDTA (carbonyl group) to form a complex compound, so that the polarity was reduced. On complexation, drivatization and extraction of acidic organic compounds in 4 g soil were performed in 4 mL acetone by the use of ultrasonic technique. Derivatization and reverse reaction of complexation reinforced each other. It was more effectively under action of ultrasonic, so a single extraction within 40 min could get preferable recovery. Soil matrix would not affect complexation and in situ derivatization when total organic carbon content was lower than 3 %. In the optimal conditions, the calibration curves showed good linearity in a wide range of 5-200 μg/kg with correlation coefficients higher than 0.99. The detection limits (S/N = 3) were less than 1 μg/kg. The spiked recoveries of different concentrations ranged from 75 to 107 % with relative standard deviations of 8-13 %. This method was suitable for acid organic compounds detection in soil, solid and plant samples.